Socio-Economic Influence of Fishermen's Families on School Dropout Rate: A Case Study in Muara Nibung Village, Central Tapanuli Regency - Shofia Fakrunnisa Simanullang; Toga Mahaji; Juliana Pebrina Siburian; Tirta Anugerah; Shofian Nanda Adiprayoga (Science, Technology, and Education Care, 2026)
A persistent issue in education, school dropout is currently a significant social issue. However, economic incentives often encourage young people to participate in family economic activities even when access to quality education remains limited. The purpose of this study is to ascertain how parents in Muara Nibung Village view the value of education for their children, what factors affect school attendance in fishing households, and how economic issues partially and concurrently affect the dropout rate of fishermen's children. This study included a sample of 89 individuals and employed a mixed methodology. The following are the study's findings: (1) Although a lack of education is not a justification for not sending their children to school, the majority of parents in Muara Nibung Village have a positive attitude toward education. They want the best education possible for their kids so they can grow up to be the best versions of themselves. The dropout rate is influenced by variables with partial significance values below 0.05, including parental education, parental occupation, child involvement in employment, children's low motivation and interest, and school atmosphere. The socio-economic circumstances of fishing families can have an impact on the dropout rate, as seen by the simultaneous influence of 92.6% on the dropout rate. The study concluded that the socio-economic circumstances of fishing households strongly influence young people's learning interests in Muara Nibung Village. Unfavorable socio-economic circumstances lead children and adolescents to learn less, thereby raising the region's school dropout rate